100 contemporary architects. - Jodidio, Philip, 1954- (Hongkong : Taschen, 2008)
Architecture at the dawn of the 21st century: the indispensable compendium This two-volume compilation brings together highlights from TASCHEN's groundbreaking title Building a New Millennium and the first four volumes of our renowned Architecture Now! books for a comprehensive study of architecture around the world at the beginning of the 21st century. Up-and-coming architects-tomorrow's superstars-are featured alongside the field's most respected practitioners, such as Santiago Calatrava, Herzog & de Meuron, Koolhaas/OMA, Daniel Libeskind, Richard Meier, Oscar Niemeyer, and Jean Nouvel.
Vol 2. : J-Z
Bevat teksten in het Engels, Duits en Frans.
Keywords: Architecture -- 20th century; Architecture -- 21st century; Architectuur -- 1990-.; Architectuur -- 2000-.